Preparation and characterization of high-Tc (YBa2Cu3O7-δ)1-x/(CNTs)x superconductors with highly boosted superconducting performances. Issue 16 (15th August 2021) - Hannachi, E.; Almessiere, M.A.; Slimani, Y.; Alshamrani, Rahaf B.; Yasin, Ghulam; Ben Azzouz, F.
Abstract: This article investigates the impact of carbon nanotubes (CNTs) addition on the morphological, structural, magnetic, and electrical transport properties of the YBa2 Cu3 O7-δ (noted YBCO) bulk system. Samples were synthesized using the solid-state reaction where the added amount of is ranging from 0.0 to 1.0 wt% of the total mass of the sample. All prepared samples were analyzed by powder X-ray diffraction (XRD) technique, scanning electron microscopy (SEM) observations, and physical property measurement system (PPMS). The structural examination via the XRD technique showed that CNTs did not affect the YBCO orthorhombic structure, but it resulted in a variation of the lattice strain. SEM observations showed a fine distribution of nanosized entities of CNTs on YBCO grains and bristles of CNTs branching out, to some extent, at the grain boundaries. The density of nanosized entities of CNTs was intensified at high concentrations. The results of electrical resistivity measurements showed that CNTs have an impact on the critical temperatures of samples. The superconducting critical temperature, T co, is slightly increased from 91.4 K in the pure sample to 91.7 K in 0.1 wt% CNTs added (S01) sample and abruptly decreased to 82.0 K for high CNTs content. The microscopic nature of samples was then examined by pseudo-gap analysis derived from excess conductivity. The critical current density ( J c m ) as well as the blocking force ( F b ) were deduced from measurements of magnetization versus applied magnetic field. Both J c m and F B were improved drastically by the addition of a small amount of CNTs. J c m increased from 0.3 × 10 4 A . c m − 2 in the pure sample to 1.3 × 10 4 A . c m − 2 in CNTs added sample. This is mainly ascribed to the active contribution of CNTs in increasing the blocking centers in the YBCO system.